Ile jest języków? - Pogonowski, Jerzy (Investigationes Linguisticae, 2007)
This is the text of a talk given on March 2, 2002 at the conference Applications of Algebra, VI in Zakopane.We share with the audience a few reflections concerning the problem of how many languages there are. Logical, mathematical, linguistic and methodological presuppositions of this question are taken into account.